Generation of Trophoblast-Like Cells From Hypomethylated Porcine Adult Dermal Fibroblasts - Arcuri, Sharon; Pennarossa, Georgia; Gandolfi, Fulvio; Brevini, Tiziana A. L. (Frontiers in Veterinary Science, 2021)
The first differentiation event in mammalian embryos is the formation of the trophectoderm, which is the progenitor of the outer epithelial components of the placenta, and which supports the fetus during the intrauterine life. However, the epigenetic and paracrine controls at work in trophectoderm differentiation are still to be fully elucidated and the creation of dedicated in vitro models is desirable to increase our understanding. Here we propose a novel approach based on the epigenetic conversion of adult dermal fibroblasts into trophoblast-like cells. The method combines the use of epigenetic erasing with an ad hoc differentiation protocol. Dermal fibroblasts are erased with 5-azacytidine (5-aza-CR) that confers cells a transient high plasticity state. They are then readdressed towards the trophoblast (TR) phenotype, using MEF conditioned medium, supplemented with bone morphogenetic protein 4 (BMP4) and inhibitors of the Activin/Nodal and FGF2 signaling pathways in low O2 conditions. The method here described allows the generation of TR-like cells from easily accessible material, such as dermal fibroblasts, that are very simply propagated in vitro. Furthermore, the strategy proposed is free of genetic modifications that make cells prone to instability and transformation. The TR model obtained may also find useful application in order to better characterize embryo implantation mechanisms and developmental disorders based on TR defects.